The 1998 floods in Bangladesh: disaster impacts, household coping strategies, and responses - del Ninno, Carlo; Dorosh, Paul A.; Smith, Lisa C.; Roy, Dilip K. (International Food Policy Research Institute, 2001)
This report combines a careful analysis of government policy and private foodgrain markets with a detailed survey of 757 households in rural Bangladesh in November and December 1998, about two months after the floodwaters receded. The report describes short- and medium-term government policy measures taken to encourage private trade, including an earlier trade liberalization that permitted private-sector imports of rice from India that stabilized private markets and largely offset the decline in production. The impact of the floods on household assets, employment, consumption, and nutritional outcomes is analyzed using the micro-level survey data. The study finds that flood-exposed households were, in general, able to avoid severe declines in food consumption and nutritional status through a combination of private-sector borrowing... and targeted government and NGO transfers.